Can Supply Chain Connectivity Effect on the Relationship between Port Performance and Economic Growth? - Insannul Kamil; Mego Plamonia; Alizar Hasan; Buang Alias (International Journal of Supply Chain Management, 2018)
In the past decade, the ports served as a node in a network of transportation, trade and global supply chain. Their roles are becoming increasingly important. Their important role in improving the efficiency and effectiveness of transport has been recognized, as well as in realizing the connectivity and competitiveness of a country. In addition, their most important role is to develop and grow national economy. This study is aimed at analyzing the relationship between the performance of the ports and the country's economic growth by having the function of mediation by supply chain connectivity. Tanjung Priok Port as the main port in Indonesia is chosen as a case study. Port performance is measured by eight indicators, while the supply chain connectivity measured by seven indicators, and national economic growth measured by the Gross Domestic Product (GDP) constructs. Linear regression analysis is used to identify the relationships developed based on three hypotheses. The study concludes that the increase of port performance has no direct effect on the countrys economic growth, but this increase affects the supply chain connectivity directly. The analysis also shows that the supply chain connectivity affects the relationship between port performance and countrys economic growth. The importance of the port for the countrys economic growth needs to be addressed with improved port performance and connectivity between ports, and it certainly demands hard efforts from the port authorities and other stakeholders.